2016
DOI: 10.1038/srep27293
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal region of Trypanosoma cruzi MASPs is antigenic and secreted via exovesicles

Abstract: Trypanosoma cruzi is the etiological agent of Chagas disease, a neglected and emerging tropical disease, endemic to South America and present in non-endemic regions due to human migration. The MASP multigene family is specific to T. cruzi, accounting for 6% of the parasite’s genome and plays a key role in immune evasion. A common feature of MASPs is the presence of two conserved regions: an N-terminal region codifying for signal peptide and a C-terminal (C-term) region, which potentially acts as GPI-addition s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 49 publications
2
39
1
Order By: Relevance
“…or T. cruzi released EVs contained both host and parasite proteins (38,40,41). Indeed, immunoelectron microscopy studies confirmed that EVs released by T. cruzi do not have a homogeneous composition, since some vesicles were found to contain the membraneanchored MASPs while other vesicle populations contained clathrin (58). Both of the latter proteins were also detected in this study (Tables S2 and S3).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…or T. cruzi released EVs contained both host and parasite proteins (38,40,41). Indeed, immunoelectron microscopy studies confirmed that EVs released by T. cruzi do not have a homogeneous composition, since some vesicles were found to contain the membraneanchored MASPs while other vesicle populations contained clathrin (58). Both of the latter proteins were also detected in this study (Tables S2 and S3).…”
Section: Discussionsupporting
confidence: 69%
“…Proteomic analysis showed that the TESA used in a number of diagnostic assays (9, 22-24) contains a mixture of Vero cell and T. cruzi proteins (see Table S1 in the supplemental material). Purified TESA EVs, which by transmission electron microscopy had a diameter of ϳ80 to 100 nm, were found to contain a preponderance of trans-sialidases, mucins, and MASPs, which may be anchored to the parasite cell surface via glycosyl phosphatidylinositol (GPI) lipid or inserted into the EV membrane via a conserved C-terminal region (58,60,61). This finding was in agreement with those of previous studies showing that trans-sialidases constitute the dominant group of proteins released by trypomastigotes in infected animals or cell cultures (32,45,62).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, and despite previous reports claiming that sorting signals (i.e. GPI-addition sequence and/or SP) of MASPs elicited strong humoral responses in chronic Chagasic patients [ 24 , 25 ], all of the Chagas-chip identified motifs lied within the mature region of MASP molecules ( Fig 4A ). Within the MASP mature regions, antigenic motifs were broadly distributed ( Fig 4B ).…”
Section: Resultscontrasting
confidence: 68%
“…In addition, MASP products were also found associated to secreted plasma membrane-derived micro-vesicles (MVs) [ 23 25 ]. Intriguingly, and even though trypanosomatids have evolved fine-tuned transport mechanisms for efficient processing and surface display of large amounts of GPI-anchored molecules [ 26 , 27 ], ‘immature’ MASPs bearing non-cleaved sorting signals were recently found inside MVs [ 24 , 25 ]. Within the central and ‘mature’ region, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The release of EVs by pathogens and their role in disease progression by modulating the host immune response has been demonstrated in several studies4041424344. In T. cruzi , the existence of proteins belonging to surface proteins within these EVs, including the highly conserved C-term region of the MASP family19 has been previously reported45464748. Additionally, EVs could be also produced by the host cell in response to the presence of the parasite.…”
mentioning
confidence: 92%